Tumor-like ovarian endometriosis with pregnancy decidua reaction: A case report and review of the literature - Yu-Rou Zhang; Zhi-Li Li; Li Guo (Journal of International Medical Research)
We describe a case of bilateral ovarian tumor-like lesions detected during pregnancy. It is important to highlight that these masses were not detected for the first time during pregnancy; the patient had already been aware of them 2 years prior, during pregnancy preparation, when an ultrasound examination revealed bilateral space-occupying ovarian lesions. These lesions did not exhibit any increase in size during regular follow-ups until pregnancy. At 17 weeks of gestation, fetal ultrasound showed significant enlargement of the bilateral ovarian lesions. The patient underwent pelvic magnetic resonance imaging, which revealed cystic masses in both the ovaries with septations and multiple nodular and flocculent projections on the walls and septations, exhibiting features resembling malignant tumors. The cystic fluid within each cyst predominantly showed slightly short T1 and long T2 signal characteristics. The final diagnosis of lesions occupying the ovarian space was endometriotic cysts with a decidual reaction associated with pregnancy, which was confirmed on postoperative pathological examination. Subsequently, at 19 weeks of gestation, the patient underwent a “laparoscopic excision of the left ovarian lesion and right ovarian lesion stripping.” The patient recovered well postoperatively and successfully delivered a baby at 39 weeks of gestation. Endometriosis with decidual reaction during pregnancy is rare and ectopic decidual tissue can easily be confused with neoplastic lesions using imaging results. In addition, clinicians must remain vigilant about the special conditions that ectopic decidual tissue may cause, such as cyst rupture, massive hemorrhage, dystocia, and even fetal death.